Cognitive status correlates of subclinical action tremor in female carriers of FMR1 premutation - Loesch, Danuta Z.; Atkinson, Anna; Hall, Deborah A.; Tassone, Flora; Stimpson, Paige; Storey, Elsdon (Frontiers in Neurology, 2024)
Background There is evidence for a significant excess of kinetic upper limb tremor in non-FXTAS female FMR1 premutation carriers. The present study explores the possibility that this tremor is associated with various other features reminiscent of those occurring in syndromic FXTAS. Sample/methods This study analyzed the data from an Australian cohort of 48 asymptomatic premutation women. We utilized spiral drawings from CRST, representing action tremor; the CRST total tremor; and ICARS- kinetic tremors/cerebellar ataxia scales. Cognitive tests (involving executive functioning) included SDMT, TMT, two subtests of the WAIS-III: MR and Similarities. Spearman Rank correlations assessed the relationships between the above measures, and the Chi-square tested hypothesis about the association between the white matter hyperintensities (wmhs) in the splenium of corpus callosum assessed from MR images and spiral drawings scores. Results The spiral drawing scores were significantly correlated with all three non-verbal cognitive test scores, and with the CRST scores; the latter correlated with all four cognitive test measures. Similarities (verbal) scores correlated with CRST, ICARS, and with the remaining cognitive scores. Ordered spiral scores’ categories were significantly associated with the degree of splenium involvement. Conclusion This study showed that, in non-FXTAS premutation female carriers, sub-symptomatic forms of kinetic tremor were associated with a broader motor, and cognitive (especially executive) dysfunction.